Does enterprise green innovation contribute to the carbon emission reduction? Evidence from China - Xie, Jiajin; Wang, Yindan (Frontiers in Environmental Science, 2024)
Green innovation serves as a driving force for enterprises to enhance their competitiveness and may offer an effective pathway for reducing carbon emissions. This study, using data on green innovation and carbon emissions from publicly listed companies between 2000 and 2022, examines the impact of green innovation on enterprise carbon emissions and its specific transmission channels. The findings reveal that: 1) Green innovation significantly reduces enterprise carbon emissions, and this inhibitory effect remains robust across a series of stability tests. 2) Mechanistically, green innovation primarily decreases carbon emissions through improvements in energy efficiency and the specialization of enterprise management. 3) Compared to the application for green utility model patents, green innovation through the application for green invention patents is more effective in reducing enterprise carbon emissions. The carbon emission reduction effect of green innovation is found to be more pronounced in non-state-owned enterprises compared to state-owned enterprises. Furthermore, when comparing the pollution intensity and technological complexity of industries, the suppressive effect of green innovation on carbon emissions is stronger for enterprises operating in highly polluting and technologically complex industries. The findings of this study provide empirical evidence to support the promotion of green innovation for facilitating the green and low-carbon transition of manufacturing enterprises in developing countries.